Philosophical explanations - Nozick, Robert (Cambridge THe Beljnap Press of harvard University Press, 1981)
In this highly original work, Robert Nozick develops new views on philosophy's central topics and weaves them into a unified philosophical perspective. It is many years since a major work in English has ranged so widely over philosophy's fundamental concerns: the identity of the self, knowledge and skepticism, free will, the question of why there is something rather than nothing, the foundations of ethics, the meaning of life.